(untitled) (Scientific journal of the Fergana State University, 2025)
In this article the dynamics of water-soluble ions change in irrigated meadow saz soils of Fergana valley under the influence of farming is studied. According to the results of analysis of water extract in genetic horizons of meadow saz soils it is proved that the amount of dry residue is transformed from non-saline group to the group of weak, medium and strong salinisation. It is proved that sulphate ion dominates in irrigated meadow saz soils, and salinisation occurs under groundwater pressure.